In situ Observation of Nucleated Polymer Crystallization in Polyoxymethylene Sandwich Composites - Slouf, Miroslav; Krejcikova, Sabina; Vackova, Tatana; Kratochvil, Jaroslav; Novak, Libor (Frontiers in Materials, 2015)
We introduce a dynamic sandwich method, which can be used for in-situ observation and quantification of polymer crystallization nucleated by micro/nanoparticles. The method was applied on polyoxymethylene (POM) composites with three nucleating agents: talc micropowder (POM/mTalc), chalk nanopowder (POM/nChalk) and titanate nanotubes (POM/TiNT). The nucleating agents were deposited between polymer films, the resulting sandwich samples were consolidated by thermal treatment, and their microtomed cross-sections were observed during isothermal crystallization by polarized light microscopy. As the intensity of polarized light was shown to be proportional to the relative crystallinity, the PLM results could be fitted to Avrami equation and the nucleating activity of all investigated particles could be quantified by means of Avrami parameters (n, k). The crystallization half-times increased reproducibly in the following order: POM/nChalk < POM/mTalc < POM/TiNT ~ POM. For strong nucleating agents (mTalc, nChalk), the crystallization kinetics corresponded to spontaneous crystallization starting from central nucleating layer, which was verified by computer simulations. The results were also confirmed by DSC. We concluded that the sandwich method is an efficient microscopic technique for detailed evaluation of nucleating activity of arbitrary micro/nanoparticles in polymer systems.